Fatigue of dented pipes - Luo, Renfan (2002)
A dented pipe fails either through being punctured or by fatigue damage accumulation due to internal pressure fluctuation. Increasing the wall thickness may prevent these failures but is impractical. As a pipe is punctured, transmission services must be cut off and repair processes have to be made immediately. However, when a dent depth is not large enough to puncture the pipe, the pipe can safely continue in service for a long time until a fatigue crack initiation occurs. Therefore, the fatigue life assessment has attracted much attention in the pipe industries for economic and safety reasons. The severe tensile residual stress concentration and the large plastic strain deformation in the dented region are the main causes of the pipe failure due to fatigue damage. Accurate calculation and prediction of the residual stress and variations resulting from internal pressure fluctuation can lead to safety assessments and prediction of the remaining life of the dented pipe. Due to the complex nature of the contact process, the deformed pipe geometry and the elastic-plasticity, analytical approaches are incapable of obtaining stress solutions. Therefore, FE modelling is employed in the present work. Experimental tests are employed to investigate the indenter force-dent depth behaviour which can be compared with the FE solutions to confirm and validate the FE models. The rigid perfect elastic-plastic limit load method and an energy-based method are also used to analytically calculate the limit load and the indenter force/deflection relationship of indented rings to predict damage. Two dimensional FE modelling is performed to calculate the contact and residual stress and strain distributions on the outer, inner surfaces and through the wall thickness. These FE solutions show that high stress concentrations occur in the indented region, which give the potential for fatigue damage. As the 2D FE modelling requires only limited resources, the indenter size and indentation position can be changed to analyse their effects on stress and strain distributions in the indented region. This forms the foundation of later 3D FE modelling. Stress sensitivity and the validation of shell models are investigated and confirmed through the 2D and 3D FE modelling and by comparing experimental test data with the FE solutions. Based on this work, the decision is made to use shell element modelling to perform the residual stress and stress range calculations in a 3D pipe. Semi-empirical formulations are developed to predict stress and stress range values if the residual dent depth, the pipe and indenter geometries, material property, internal pressure and pressure range are known. These FE solutions and semi-empirical formulae can be used to calculate the stress range and mean stress.